Regulação do sistema peptídeos natriuréticos nas células da granulosa e do cumulus na foliculogênese em bovinos - De Cesaro, Matheus Pedrotti (2017)
This thesis aims to contribute to the knowledge of the regulation and function of the natriuretic peptide (NP) system during follicular dominance, ovulation, oocyte meiosis resumption and cumulus cells expansion in cattle. In the first study, the NP system was characterized in bovine COC. Moreover, NPPA and NPPC increased cGMP levels in cumulus cells and oocyte after 3 hours of culture, preventing the increase of cAMP in oocyte in the presence of forskolin. In the second study, using in vivo experimental models, none of the three NPs were detected in the granulosa cells during follicular deviation in cattle. However, NPR-3 is highly expressed at the expected time of follicular deviation, and all three NP receptors are expressed in granulosa cells of the dominant follicle. FSH injection maintained the expression of the three NP receptors after follicular deviation in the largest and second largest follicles. However, only NPR-1 mRNA decreased after inhibition of estradiol receptors by intrafollicular injection of fulvestrant. In the granulosa cells of pre ovulatory follicles, only NPPB mRNA was not detected. Nevertheless, after the administration of a GnRH analog, NPPC mRNA expression increased within 3 and 6 hours and NPR-3 mRNA gradually decreased after 3 hours. NPPA and NPR-2 mRNA was not regulated by GnRH, but NPR-1 mRNA increased at 24 hours after GnRH. In the third study, abundance of mRNA for NPR-1, NPR-2 and NPR-3 was not altered by LH and/or AG1478 (EGFr inhibitor) after 6 hours of culture in vitro. Also, LH stimulated NPPC mRNA expression and AG1478 prevented this increase in granulosa cultured in vitro. To confirm the in vitro results, was used an in vivo model and observed that the NPPC mRNA expression increased and NPR-3 mRNA decreased in granulosa cells after 6 hours of GnRH challenge. However, intrafollicular injection of AG1478 prevented the effect of GnRH on NPPC and NPR-3 mRNA expression. In addition, it we obseved that ANP in association with LH stimulated COX2 expression in comparison with LH alone or absence of this gonadotropin. It was observed that the EGFr blockade in vivo did not prevent ovulation in cattle. In the fourth study, it was observed that NPR-3 mRNA expression decreases in bovine cumulus cells after treatment of COCs with FSH or FSH+LH via EGFr. Forskolin, an adenylate cyclase stimulator, also decreased NPR-3 mRNA expression in cumulus cells. Expression of NPR-1 mRNA was very low in bovine cumulus cells and NPR-2 mRNA was not regulated in the proposed treatments. In addition, it was observed that the activation of NPR-3 by a specific agonist (cANP4-23) did not interfere in bovine oocyte nuclear maturation, but it inhibited the complete expansion of cumulus cells FSH+LH-stimulated. Additionally, the association of cANP4-23 with CNP further decreased cumulus cell expansion.